Analysis of Corporate Social Responsibility: Issue and Challenges: Understanding the Scope and Definitions of Corporate Social Responsibility (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Over the past few years CSR, as a concept, has been the focus of many deliberations and research. It has grown in importance both academically as well as in the business sense. It captures a spectrum of values and criteria for measuring a company’s contribution to social development. As the term “CSR” is used constantly, many harmonizing and overlapping concepts, such as business citizenship, business beliefs, stakeholder management and sustainability, have emerged. These extensive ranges of synonymously used terms indicate that multiple definitions have been devised for CSR, mostly from different perspectives and by those in facilitating roles such as the corporate sector, government agencies, academics and the public sector. The European Union (EU) has used definition of CSR in the business and social context. It describes CSR as “the accountability of the business enterprises towards the stakeholders. It is the continuing commitment by business to behave fairly and responsibly, and contribute to economic development while improving the quality of life of the work force and their families as well as of the local community and society at large”